(untitled) (Global Journal of Medical Research, 2020)
Quality of life in burn survivors is determined on the basis of functional outcome of hand. After burn injury, deformities are observed in surgical practice and even post burn contracture is one of the common deformities. These deformities are generally managed surgically like release of contracture followed by skin graft or skin flap. In present time variety of operative techniques are accessible for surgeons and even which particular operative technique will be more useful for particular type of deformity that is also decide by surgeon. Present case report deals with a patient of 9 years having complaints of deformed and fused fingers of left hand with loss of movements. Inadequate management and ignorance of parents resulted into severe post burn contractures. Detailed history and examination revealed that contracture release and a left groin full thickness common island grafting for all the fingers was done in a medical college. She was having syndactyly of all four digits as a result of common full thickness skin graft with residual contractures. Two stage surgical interventions were planned to release this acquired syndactyly and the contractures. This two stage surgical intervention culminated in complete correction of the syndactyly along with release of contractures.